The dollar and the international monetary system - Hansen, Alvin H. (New York : McGraw-Hill Book Co., 1965)
The most widely accepted definition of disequilibrium had been an adverse balance of payments as evident in substantial losses of reserves or a decline in external value of the currency, or both.
Includes index
Bibliographical footnotes.
II 16/01/2019
Loans
Keywords: Gold standard; Currency question